Patterns and trends of medicinal poisoning substances: a population-based cohort study of injuries in 0-11 year old children from 1998-2018 - Edward G Tyrrell; Elizabeth Orton; Laila J Tata; Denise Kendrick (BMC, 2024)
Abstract Background There have been sharp increases in antidepressant and opioid prescriptions over the last 10 years, as well as increased over-the-counter medicine availability. However, the impact on childhood medicinal poisonings rates, particularly by socioeconomic deprivation is unclear. This study reports population level medicinal poisoning substance patterns in England among children aged 0-11 years, helping inform safety advice and poisoning prevention interventions. Methods An open cohort study of 1,489,620 0-11 year olds was conducted from 1998 to 2018, using the Clinical Practice Research Datalink, to examine inpatient hospital admissions for poisoning. Incidence rates and adjusted incidence rate ratios (aIRR) were calculated for poisoning substance groups by age, sex, socio-economic deprivation and year. Results 3,685 medicinal poisoning hospital admissions were identified. The most common substances were paracetamol (33.2%), dependence/withdrawal risk drugs (DWRD - antidepressants, opioids, gabapentinoids, benzodiazepines) (13.5%) and other over-the-counter (OTC) analgesics/anti-common cold drugs (13.0%). Over the study period DWRD poisonings decreased 33% (aIRR 0.67, 95%CI 0.50-0.90 comparing 2013/14-2017/18 to 1998/99-2002/03), while paracetamol poisonings increased 43% (aIRR 1.43, 95%CI 1.20-1.70 for the same periods), with no change in incidence rates for other OTC drugs (aIRR 0.82, 95% CI 0.60-1.12) or all medications combined (aIRR 0.97, 95%CI 0.88-1.07). A gradient in poisonings by area-level socioeconomic deprivation was shown for all medications (aIRR 1.32, 95%CI 1.18-1.47 for most deprived compared to least deprived quintile), and DWRDs (aIRR 2.03, 95%CI 1.42-2.88 for 4th most deprived quintile and aIRR 1.88, 95%CI 1.32-2.66 for 5th most deprived quintile, compared to least deprived quintile), but not for paracetamol or other OTC drug poisonings. Conclusions Poisonings from DWRDs decreased by 33%, while paracetamol poisonings increased by 43% during the study period. There was a gradient by area-level socioeconomic deprivation in prescribed medication poisonings, including drugs with withdrawal/dependence risk, but not OTC medication poisonings. Households in more socioeconomically deprived areas have the potential to benefit most from measures to improve safe storage of medicines and are likely to require targeted interventions providing education and safety equipment. In addition, universal promotion of the safe storage of OTC and prescribed medicines must be provided by prescribers, community pharmacies and other outlets of such medication.